Marine Dinoflagellate Assemblage in the Galápagos Marine Reserve - Carnicer, Olga; De La Fuente, Patricia; Canepa, Antonio; Keith, Inti; Rebolledo-Monsalve, Eduardo; Diogène, Jorge; Fernández-Tejedor, Margarita (Frontiers in Marine Science, 2019)
It is likely that harmful algal blooms have increased in frequency, intensity and geographic distribution in the last decades in response to anthropogenic activities. The Galápagos Islands are renowned for their exceptional biological diversity; however, marine dinoflagellate communities have not been represented in biodiversity assessments. Therefore, this study aims to provide key information about dinoflagellate diversity and abundances, with special attention to harmful species, during a weak La Niña event in the Galápagos Marine Reserve (GMR). The study was performed during March-April 2017 and four transects were conducted at four Islands (Santa Cruz, Santa Fé, Seymour and Pinzón) representing the southern region of the GMR. Water net samples were collected at 2, 5 and 10 nautical miles (nm) from the coast, at a total of 48 sampling sites. The presence of toxic species, and their cell abundance was estimated in seven transects at 0, 15 and 30 meters of depth. A total of 152 taxa belonging to 7 orders, 22 families, and 38 genera were registered. The number of taxa found is almost three times higher than the maximum observed in previous studies. Dinoflagellate species richness among stations ranged between 53 and 23 taxa and was higher in northern sites. From the applied cluster analysis, five dinoflagellate assemblages were identified as a discrete community structure, one was found only in Santa Fé Island, which is probably related to the presence of the Equatorial Undercurrent (EUC). Regarding cell abundance estimations, low abundances were registered throughout the sampling sites and no blooms were detected. Higher abundances were registered in the northern transects coinciding with one of the most productive areas of the archipelago, situated north of Santa Cruz. Among the identified taxa, 19 of them were potentially toxic, including epiphytic species, allowing the possibility of blooms in benthic areas. This study presents the first record of several dinoflagellate species in the area (both non-toxic and harmful species) and thus, emphasizing the need for the implementation of phytoplankton monitoring programs by the government to prevent potential ecological, sanitary and economic impacts in the GMR.